Proceedings of the 20th International Symposium on Advancement of Construction Management and Real Estate - Wu, Yuzhe; Zheng, Sheng; Luo, Jiaojiao; Wang, Wei; Mo, Zhibin; Shan, Liping (Springer, 2016)
These conference proceedings offer an outstanding resource for academics and professionals, sharing essential findings on the latest developments in real estate and construction management. The subject is "Advancement of Construction Management and Real Estate" in the context of new-type urbanization. The Chinese Research Institute of Construction Management (CRIOCM), working in close collaboration with Zhejiang University, organized CRIOCM2015, the 20th International Symposium. Written by academics and professionals from all over the world, these proceedings discuss the latest achievements, research outputs and advances between frontier disciplines in the field of construction management and real estate. They cover a wide range of topics, including new-type urbanization, land development and land use, urban development and management, the real estate market and housing policies. The discussions will provide an important reference source on the implementation of new-type urbanization in China and abroad.